2012
DOI: 10.1007/s00424-011-1071-x
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 and TRPV4 mediate paclitaxel-induced peripheral neuropathy in mice via a glutathione-sensitive mechanism

Abstract: Paclitaxel produces a sensory neuropathy, characterized by mechanical and cold hypersensitivity, which are abated by antioxidants. The transient receptor potential vanilloid 4 (TRPV4) channel has been reported to contribute to paclitaxel-evoked allodynia in rodents. We recently showed that TRP ankyrin 1 (TRPA1) channel mediates oxaliplatin-evoked cold and mechanical allodynia, and the drug targets TRPA1 via generation of oxidative stress. Here, we have explored whether TRPA1 activation contributes to paclitaxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
188
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 200 publications
(198 citation statements)
references
References 45 publications
10
188
0
Order By: Relevance
“…By both genetic and pharmacological approaches, we showed that TRPA1 entirely mediates mechanical and cold hypersensitivity induced by oxaliplatin and cisplatin [146] in mice and rats. We confirmed [103] that TRPV4 mediates part of the mechanical hyperalgesia induced by paclitaxel [74], and we showed that TRPV4-resistant mechanical hyperalgesia was exclusively mediated by TRPA1 [103]. We also discovered that paclitaxel-induced cold allodynia was completely due to TRPA1 activation [103].…”
Section: Trpa1supporting
confidence: 64%
See 4 more Smart Citations
“…By both genetic and pharmacological approaches, we showed that TRPA1 entirely mediates mechanical and cold hypersensitivity induced by oxaliplatin and cisplatin [146] in mice and rats. We confirmed [103] that TRPV4 mediates part of the mechanical hyperalgesia induced by paclitaxel [74], and we showed that TRPV4-resistant mechanical hyperalgesia was exclusively mediated by TRPA1 [103]. We also discovered that paclitaxel-induced cold allodynia was completely due to TRPA1 activation [103].…”
Section: Trpa1supporting
confidence: 64%
“…We confirmed [103] that TRPV4 mediates part of the mechanical hyperalgesia induced by paclitaxel [74], and we showed that TRPV4-resistant mechanical hyperalgesia was exclusively mediated by TRPA1 [103]. We also discovered that paclitaxel-induced cold allodynia was completely due to TRPA1 activation [103]. One final common pathway activated by the otherwise chemically heterogeneous group of molecules, such as chemotherapeutic agents, is the production of oxidative stress in different tissues and cells [147,148] and, through this effect they can potentially activate and/or sensitize the TRPA1 channel.…”
Section: Trpa1supporting
confidence: 61%
See 3 more Smart Citations